2019
DOI: 10.3390/electronics8111256
|View full text |Cite
|
Sign up to set email alerts
|

Open Electronics for Medical Devices: State-of-Art and Unique Advantages

Abstract: A wide range of medical devices have significant electronic components. Compared to open-source medical software, open (and open-source) electronic hardware has been less published in peer-reviewed literature. In this review, we explore the developments, significance, and advantages of using open platform electronic hardware for medical devices. Open hardware electronics platforms offer not just shorter development times, reduced costs, and customization; they also offer a key potential advantage which current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…Existing literature usually assumes that companies, startups, or academic labs manufacture OSH devices (Li & Seering, 2019;Pandey & Vora, 2019). But the emergence of the OSH movement in the medical field led the Food and Drug Administration (FDA), in charge of medical device certification in the United States, to change their policies.…”
Section: Medical Device Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing literature usually assumes that companies, startups, or academic labs manufacture OSH devices (Li & Seering, 2019;Pandey & Vora, 2019). But the emergence of the OSH movement in the medical field led the Food and Drug Administration (FDA), in charge of medical device certification in the United States, to change their policies.…”
Section: Medical Device Regulationmentioning
confidence: 99%
“…It allowed decentralized production of respirators, visors, and spare parts as a rapid response to emergency needs (Maia Chagas, Molloy, Prieto-Godino, & Baden, 2020). Furthermore, making hardware design available under an open-source license allows anyone to contribute and improve the device, thus accelerating innovation at a fraction of the cost (Pandey & Vora, 2019;Pearce, 2015b;Williams, Gibb, & Weekly, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of single board architectures integrating sensors technologies and their applications has led to different tutorials, overviews, reviews and surveys papers being reported in the literature, included on-line publications, white papers, webinars and different aspects, topics and points of view: SoC technologies, process capacity, characteristics, power and number of I/O, in terms of cost, control flexibility, among others. In this sense SBAs and ISTs for visual sensor networks are revised and analyzed in [ 87 , 88 ], transport technologies and related applications in [ 89 , 90 ] including tracking, monitoring and lighting in [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ], SBAs and ISTs for smart cities applications in [ 99 , 100 ], education and research projects in [ 101 , 102 , 103 , 104 , 105 ], medical devices in [ 106 , 107 , 108 ], smart and advanced sensors in [ 109 , 110 , 111 , 112 , 113 ], including wireless sensors [ 114 ], IoT applications in [ 115 , 116 , 117 , 118 ], smart home in [ 119 , 120 , 121 , 122 ], energy in [ 123 , 124 , 125 ], engineering education in [ 126 , 127 , 128 ], Hybrid Electric Vehicle (HEV), Fuel Cell Electric Vehicles (FCEV) and Plug-in-Hybrid Electric Vehicle (PHEV) in [ 129 ,…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound-based techniques and systems are nowadays exploited in several very different areas. Biomedical investigations [1][2][3][4][5], non-destructive tests (NDT) [6][7][8], ultrasound levitation [9], nuclear safety [10], industrial monitoring of production processes [11][12][13], robotics [14], Doppler investigations [15], personal identification [16], and oil industry [17] are just a few examples of the employments that confirm the widespread presence of ultrasounds in our modern world. Although high-end systems, like clinical or research echograph [18][19][20], employ hundreds of independent ultrasound channels and require specific frond-end electronics [21,22], most of the aforementioned applications are based on a single ultrasound channel, and are preferably realized through discrete electronic devices.…”
Section: Introductionmentioning
confidence: 99%